ANALISIS KEGIATAN PEMBELAJARAN, FASILITAS, DAN LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA SMP MASTER DEPOK - Nurlina Nurlina; Faridah Faridah; Yopy Ratna Dewanti (JURNAL LENTERA BISNIS, 2020)
Master School stands for Masjid Terminal School. It’s a school with free tuition for the street children located in Depok Integrated Station. There are 5 (five) parties as the main target of the Master School. They are abandoned children, street children, children with special needs, children against the law and disabilities children who came from underprivileged families. They consist of 2000 students who learn there with container as the facilities of class room. There are things as the concern of the Master School Depok, such as the learning process, facilities and the school environment. The effect of the learning process towards students’ character building of SMP Master Depok, based on the statistic’s result, it can be stated that Master Depok students is partially significant in knowledge mastery of the subject lesson, improving attitude and behaviour during teaching and learning process, skills achieved of each subject. The school facilities towards character building based on the statistic’s result affects partially significant for the availability of the class, the headmaster’s office, the teachers’ room, the restroom, the mosque (mushola) or worship place. The school environment towards character building based on the statistics’ resultaffects partially significant from the activities that lead students to religious, activities foster students to discipline. The learning process, facilities and school environment, based on the statistics’ result affects simultaneously significant towards students’ character building.Keywords : Depok Master High School Students, Character Building, Learning  Process,Facilities, School Environment